Integration of AI Tools in Islamic Pedagogy: Opportunities and Challenges for Contemporary PAI Teachers - Shelly Arsita; Mukhlizar , Mukhlizar; Dedy Novriadi; Syukri Amin; N. Baskautshar (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2025)
This study explores how Islamic Religious Education (Pendidikan Agama Islam / PAI) teachers integrate artificial intelligence (AI) tools into their pedagogy, and identifies the opportunities and challenges that arise. Using a descriptive qualitative design, data were collected through semi-structured online interviews with five PAI teachers at SMA Negeri 4 Bengkulu, Indonesia, all of whom had prior experience using AI-based applications in lesson planning or teaching. Thematic analysis revealed that AI is primarily used in “back-end” domains of instruction: generating lesson outlines, designing assessment items, and developing presentation media, with more limited and carefully supervised use in student-facing activities. Teachers reported clear benefits, including increased efficiency in preparing materials, more varied explanations and examples of Islamic concepts, and simple forms of differentiation for students with different levels of readiness. However, they also expressed strong concerns about the theological accuracy of AI-generated content, the risk of plagiarism and student over-reliance, unequal access to devices and internet, and the potential erosion of the teacher’s role as murabbi and moral model. Overall, the findings suggest that AI in Islamic pedagogy is best positioned as a supportive tool, filtered through Islamic sources and teacher judgment, to strengthen rather than weaken the core aims of PAI.